A new look at methane and nonmethane hydrocarbon emissions from oil and natural gas operations in the Colorado Denver‐Julesburg Basin. Issue 11 (3rd June 2014) - Pétron, Gabrielle; Karion, Anna; Sweeney, Colm; Miller, Benjamin R.; Montzka, Stephen A.; Frost, Gregory J.; Trainer, Michael; Tans, Pieter; Andrews, Arlyn; Kofler, Jonathan; Helmig, Detlev; Guenther, Douglas; et al.
Abstract Emissions of methane (CH4) from oil and natural gas (O&G) operations in the most densely drilled area of the Denver‐Julesburg Basin in Weld County located in northeastern Colorado are estimated for 2 days in May 2012 using aircraft‐based CH4 observations and planetary boundary layer height and ground‐based wind profile measurements. Total top‐down CH4 emission estimates are 25.8 ± 8.4 and 26.2 ± 10.7 t CH4/h for the 29 and 31 May flights, respectively. Using inventory data, we estimate the total emissions of CH4 from non‐O&G gas‐related sources at 7.1 ± 1.7 and 6.3 ± 1.0 t CH4/h for these 2 days. The difference in emissions is attributed to O&G sources in the study region, and their total emission is on average 19.3 ± 6.9 t/h, close to 3 times higher than an hourly emission estimate based on Environmental Protection Agency's Greenhouse Gas Reporting Program data for 2012. We derive top‐down emissions estimates for propane, n‐butane, i‐pentane, n‐pentane, and benzene from our total top‐down CH4 emission estimate and the relative hydrocarbon abundances in aircraft‐based discrete air samples. Emissions for these five nonmethane hydrocarbons alone total 25.4 ± 8.2 t/h. Assuming that these emissions are solely originating from O&G‐related activities in the study region, our results show that the state inventory for total volatile organic compounds emitted by O&G activities is at least a factor of 2 too low for May 2012. Our top‐down emission estimate of benzene emissions from O&G operations is 173 ± 64 kg/h, or 7 times larger than in the state inventory.